Voluntary Medical Male Circumcision Scale-Up in Nyanza, Kenya: Evaluating Technical Efficiency and Productivity of Service Delivery - Omondi Aduda, Dickens S. (PLoS One, 2015)
BACKGROUND: Voluntary medical male circumcision (VMMC) service delivery is complex and resource-intensive. In Kenya’s context there is still paucity of information on resource use vis-à-vis outputs as programs scale up. Knowledge of technical efficiency, productivity and potential sources of constraints is desirable to improve decision-making. OBJECTIVE: To evaluate technical efficiency and productivity of VMMC service delivery in Nyanza in 2011/2012 using data envelopment analysis. DESIGN: Comparative process evaluation of facilities providing VMMC in Nyanza in 2011/2012 using output orientated data envelopment analysis. RESULTS: Twenty one facilities were evaluated. Only 1 of 7 variables considered (total elapsed operation time) significantly improved from 32.8 minutes (SD 8.8) in 2011 to 30 minutes (SD 6.6) in 2012 (95%CI = 0.0350–5.2488; p = 0.047). Mean scale technical efficiency significantly improved from 91% (SD 19.8) in 2011 to 99% (SD 4.0) in 2012 particularly among outreach compared to fixed service delivery facilities (CI -31.47959–4.698508; p = 0.005). Increase in mean VRS technical efficiency from 84% (SD 25.3) in 2011 and 89% (SD 25.1) in 2012 was not statistically significant. Benchmark facilities were #119 and #125 in 2011 and #103 in 2012. Malmquist Productivity Index (MPI) at fixed facilities declined by 2.5% but gained by 4.9% at outreach ones by 2012. Total factor productivity improved by 83% (p = 0.032) in 2012, largely due to progress in technological efficiency by 79% (p = 0.008). CONCLUSIONS: Significant improvement in scale technical efficiency among outreach facilities in 2012 was attributable to accelerated activities. However, ongoing pure technical inefficiency requires concerted attention. Technological progress was the key driver of service productivity growth in Nyanza. Incorporating service-quality dimensions and using stepwise-multiple criteria in performance evaluation enhances comprehensiveness and validity. These findings highlight site-level resource use and sources of variations in VMMC service productivity, which are important for program planning.